2016
DOI: 10.7717/peerj.1920
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sound exposure on the growth and intracellular macromolecular synthesis ofE. colik-12

Abstract: Microbes, as one of the primary producers of the biosphere, play an important role in ecosystems. Exploring the mechanism of adaptation and resistance of microbial population to various environmental factors has come into focus in the fields of modern microbial ecology and molecular ecology. However, facing the increasingly serious problem of acoustic pollution, very few efforts have been put forth into studying the relation of single cell organisms and sound field exposure. Herein, we studied the biological e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…This biological effect of intermittence can be explained if physical stress mechanoreceptor channels are considered as the mechanism by which E. coli detects sound channels . A continuous complex stimulus may saturate the response of the mechanoreceptor channels making them unresponsive, in a very similar way to the onset of insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This biological effect of intermittence can be explained if physical stress mechanoreceptor channels are considered as the mechanism by which E. coli detects sound channels . A continuous complex stimulus may saturate the response of the mechanoreceptor channels making them unresponsive, in a very similar way to the onset of insulin resistance.…”
Section: Resultsmentioning
confidence: 99%
“…It has already been reported that sound enhances biomass growth in E. coli. [8][9][10]16 However, in previous reports, a clear correlation between individual sound elements and the response (biomass concentration) could not be concluded as the treatments consisted of complex musical compositions or they merely focused on frequency.…”
Section: Effect Of Individual Sound Elements Over Biomass Concentratimentioning
confidence: 99%
See 2 more Smart Citations
“…Though the interaction of microbial cells with audible range of sound has not been researched much, there are quite a few reports (Aggio et al, 2012;Cai et al, 2015;Sarvaiya and Kothari, 2015;Gu et al, 2016;Shah et al, 2016) describing microbial growth and metabolism getting affected by sound stimulation. Whether microbes respond to sonic stimulation in a frequency-dependent fashion, is an interesting problem to investigate.…”
Section: Introductionmentioning
confidence: 99%